Association Between Longitudinal Changes in Left Ventricular Structure and Function and 24‐Hour Urinary Free Cortisol in Essential Hypertension - Gao‐Zhen Cao; Jia‐Yi Huang; Qing‐Shan Lin; Run Wang; Cong Chen; Jian‐Cheng Xiu; Kai‐Hang Yiu (The Journal of Clinical Hypertension)
ABSTRACT This study aimed to investigate the associations between 24‐hour urinary cortisol levels (24 h‐UFC) and alterations in left ventricular (LV) structure and function in patients with essential hypertension. A prospective cohort study was conducted, including 315 patients with essential hypertension who underwent baseline 24 h‐UFC measurement and echocardiographic evaluation of left ventricular mass (LVM), left ventricular ejection fraction (LVEF), and the E/e′ ratio. Over a mean follow‐up period of 28.54 ± 14.21 months, patients were grouped into tertiles based on baseline 24 h‐UFC levels. Higher baseline 24 h‐UFC levels were significantly associated with greater increases in LVM and E/e′, reflecting adverse LV remodeling and diastolic dysfunction. These associations persisted after adjusting for potential confounders, including age, gender, baseline blood pressure, and their changes during follow‐up. Moreover, patients in the highest 24 h‐UFC tertile showed an increased prevalence of LV hypertrophy, contrasting with a reduction observed in the lower tertiles. These findings underscore the independent role of elevated 24 h‐UFC levels in driving adverse cardiac structural and functional changes in essential hypertension.